The impact of health literacy: associations with disease activity and medication prescription in patients with rheumatoid arthritis - Gorter, Anne; Bakker, Mark M; ten Klooster, Peter M; Boonen, Annelies; Vonkeman, Harald E (Rheumatology (Oxford, England), 2023)
Abstract Objective The aim of this study was to explore the longitudinal associations between health literacy profiles and disease activity and medication prescription in patients with RA. Methods Patients with RA who previously completed the Health Literacy Questionnaire (HLQ) and were assigned 1 of 10 distinct health literacy profiles based on cluster analysis were further aggregated into three groups: ‘several health literacy limitations’, ‘some health literacy limitations’ and ‘good health literacy’. Linear mixed modelling (LMM) was used to analyse the association between health literacy groups and disease activity over the course of 1 year. Chi-squared tests and logistic regression analyses were used to compare medication prescriptions between the groups. Results A total of 108 patients with RA were included. LMM showed a significant effect of health literacy group on disease activity over time (P = 0.010). Patients with ‘good health literacy’ had significantly lower disease activity over time [28-joint DAS with ESR (DAS28-ESR) = 2.4] than patients with ‘several health literacy limitations’ (DAS28-ESR = 3.1), independent of age, gender and education level. Patients with ‘good health literacy’ were most often prescribed a biologic DMARD (50%), whereas patients with ‘some health literacy limitations’ more commonly received a conventional synthetic DMARD only [72.7%; odds ratio (OR) 4.24], and patients with ‘several health literacy limitations’ were more often prescribed prednisolone (52.4%; OR 3.56). Conclusion Significant differences in longitudinal disease activity and medication prescription were observed between groups with different health literacy levels. These results stress the importance of insights into the role of health literacy in treatment and outcomes in patients with RA.